Después del sábado (2026)
‘Después del sábado’ is a feature-length screenplay that tells the story of Catalina, a young woman completing her nursing internship in the gynecology and obstetrics department of a public hospital in downtown Bogotá. Her goal is to earn a scholarship to pursue a master’s degree in health management abroad, allowing her to advance professionally and eventually escape her difficult economic situation. Her plans are jeopardized when she faces an unplanned pregnancy due to the failure of her contraceptive method. Torn between fear and doubt—and with time against her—Catalina experiences a spontaneous miscarriage just before deciding, confronting the emotional weight of loss. Catalina faces the difficulties of grief and the struggles of being a young woman questioning motherhood. The prejudices of her close circle, the social expectations, and the bureaucratic obstacles within the very healthcare system she works for become part of her daily battle. The aim of this screenplay is to reflect on motherhood: is it an obligation imposed by society, or a choice driven by conviction, desire, and personal vocation?